Guarding net effects on landings and discards in Mediterranean trammel net fishery: Case analysis of Egadi Islands Marine Protected Area (Central Mediterranean Sea, Italy) - Sardo, Giacomo; Vecchioni, Luca; Milisenda, Giacomo; Falsone, Fabio; Geraci, Michele Luca; Massi, Daniela; Rizzo, Pietro; Scannella, Danilo; Vitale, Sergio (Frontiers in Marine Science, 2023)
Discards remain among the main negative impacts of fishing activities, and their reductions are strengthened by the European Common Fisheries Policy (European Regulation 1380/2013). Trammel net fisheries appear more sustainable compared with other fishing techniques, especially from an ecological viewpoint. Despite this, reports show that trammel net fisheries deliver discard quantities between 10% and 43% of the total catch biomass. To supplement existing information, this current work attempts to address the discard reduction using guarding net in the small-scale fisheries of Egadi Islands MPA (Western Sicily, Central Mediterranean Sea). To assess the reduction of unwanted catches, 48 experimental fishing trials were conducted within a 6-month period. The experimental fishing trial employed a trammel net made up of 20 panels alternated with two different net configurations. The control panels (CN) held a large outer (180 mm) and small inner (31.25 mm) meshes. The test panels (GN) with guarding net constituted a three-mesh-high (50-mm mesh size) net placed between trammel net panels and a lead line. A total of 3,310 individuals belonging to 106 taxa and nine phyla were caught. Crustaceans were the most abundant unwanted catches in the control panels, whereas bioconstructions occurred in the guarding net panels. The discard ratios of CN and GN panels were statistically different (t-value = –2.55; p< 0.05). The analysis of catch per unit effort showed higher catches of CN panels for both commercial and discard fractions (p< 0.05). Moreover, the guarding net panels caught the main discarded species at 20% lower compared with the control. The overall value of the catch at the CN panels (€ 3,366.90) was higher than the total income (€ 2,043.70) generated using the GN panels, which suggests a significant commercial loss of 40% (p< 0.05).